2010
DOI: 10.3109/13693780903373811
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of terbinafine compared to lanoconazole and luliconazole in the topical treatment of dermatophytosis in a guinea pig model

Abstract: The in vivo efficacy of terbinafine was compared to lanoconazole and luliconazole in the topical treatment of dermatophytosis caused by Trichophyton mentagrophytes using a guinea pig model. Topical antifungal treatment commenced three days post-infection, and each agent was applied once daily for seven consecutive days. Upon completion of the treatment period, evaluations of clinical and mycological efficacies were performed, as was scanning electron microscopy (SEM) analyses. Data showed that while all tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 13 publications
2
18
1
Order By: Relevance
“…In vitro studies with a limited number of isolates have also reported potent activity of this agent against dermatophytes and other causative agents of dermatophytosis, including onychomycosis (8)(9)(10). Results from animal models and small clinical studies have also suggested in vivo efficacy against dermatophytosis (11)(12)(13). Our objective was to measure the in vitro activity of luliconazole against dermatophytes isolated at screening from toenails in an ongoing phase 2b/3 study of patients with mild to moderate toenail onychomycosis (www.clinicaltrials.gov, identifier NCT01431820).…”
mentioning
confidence: 99%
“…In vitro studies with a limited number of isolates have also reported potent activity of this agent against dermatophytes and other causative agents of dermatophytosis, including onychomycosis (8)(9)(10). Results from animal models and small clinical studies have also suggested in vivo efficacy against dermatophytosis (11)(12)(13). Our objective was to measure the in vitro activity of luliconazole against dermatophytes isolated at screening from toenails in an ongoing phase 2b/3 study of patients with mild to moderate toenail onychomycosis (www.clinicaltrials.gov, identifier NCT01431820).…”
mentioning
confidence: 99%
“…Recently, in vitro antifungal susceptibility testing of lanoconazole and luliconazole demonstrated potent efficacy against Trichophyton rubrum and Epidermophyton floccosum (9)(10)(11)(12)(13)(14). In addition, animal studies and small human series suggested that luliconazole and lanoconazole are effective in treating dermatophytosis and onychomycosis (15,16). Only limited data on the in vitro activity of lanoconazole and luliconazole against Aspergillus species are available.…”
mentioning
confidence: 99%
“…The total score for any treatment group signifies the average clinical score from animals in the same group. 21 …”
Section: Animal Grouping and Dosingmentioning
confidence: 99%
“…An animal infection model of dandruff was performed according to protocol of Tatsumi et al 20 and Ghannoum et al 21 with little modification. Before inoculation, the hairs of both flanks at upper left side and lower right side skin (3 cm ×3 cm) of each rat were removed by electric hair clipper (MOSER, Germany) followed by the application of hair remover cream for complete removal of hairs.…”
Section: In Vivo Efficacy Of Ag Nano Animal Model For Dandruffmentioning
confidence: 99%